SIFAT FISIK DAN MEKANIK KAYU JELUTUNG (DYERA COSTULATA HOOK F.) YANG DIDENSIFIKASI BERDASARKAN SUHU DAN WAKTU KEMPA - Pinna L., .; Usman, Fadillah H.; Yani, Ahmad (JURNAL HUTAN LESTARI, 2016)
Demand for wood has increased, while timber production decreased, in particular high quality wood. Therefore necessary the technology to improve low quality wood (III-V) such as Jelutung (Dyera Costulata Hook. F.) using with densification wood. There are two treatments used in this research, namely temperature press (1600 C, 1700 C and 1800 C) and pressing time (50 minutes, 60  minutes and 70 minutes). Sampleswere made of Jelutung wood with size30 cm (L) x 8 cm (W) x 4 cm (H).It steamed at 1200 C and hot pressed with a 30% target thicknes.Physical(color and impression of rabbah, water content, density and dimensional changes) and mechanical (MOE, MOR and  MCS) properties testing refers to British Standard Methods No.373 (1957). Results of research have shown that densification can improve the physical and mechanical properties of Jelutung wood. This research also pointed out that the treatment temperature press 1800 C and pressing time 70 minutes was the best treatment. Keywoard : Densification, Dyera Costulata Hook. F, physical and mechanical.